PENGARUH PELATIHAN DIGITALPRENEUR TERHADAP KINERJA PEMASARAN UMKM MELALUI MARKETPLACE DI DESA MANGKAI LAMA KECAMATAN LIMA PULUH KABUPATEN BATUBARA - Azzahra , Fanisa; Rahmadani, Arinil Mardhiah; Lamsiah, Puteri; Sukiati, Sukiati (Jurnal Pengabdian Masyarakat Sabangka, 2025)
The advancement of digital technology has driven economic transformation, including within the MSME sector. However, low digital literacy and limited MSME capacity in rural areas continue to hinder competitiveness. This study was conducted in Mangkai Lama Village, Lima Puluh District, Batu Bara Regency, to analyze the effect of Digitalpreneur Training on MSME marketing performance. The research employed a quantitative associative method with purposive sampling involving 30 respondents. Data were collected using a Likert scale questionnaire (1–5) and analyzed through validity and reliability tests, classical assumption tests, and simple linear regression using SPSS. The findings show that Digitalpreneur Training significantly influences marketing performance, evidenced by a t-value of 8.104 and a significance level of 0.000. The R² value of 0.701 indicates that the training contributes 70.1% to improving MSME marketing performance through the marketplace.